2011
DOI: 10.1007/s11307-011-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of 2-deoxy-2-[18F]Fluoro-D-Glucose and 3′-deoxy-3′-[18F]-Fluorothymidine Uptake in Human Tumor Xenograft Models

Abstract: When evaluating imaging biomarkers in response to therapy, the choice of tumor model should take into account in vivo baseline radiotracer uptake, which can vary significantly between models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Ki-67 is an excellent immunohistochemical marker for proliferating cells and is exclusively present during all active phases of the cell cycle (G(1), S, G(2), and mitosis) but not in resting cells (G(0)) (36). Keen et al reported a strong correlation between 18 F-FLT uptake, tk-1 expression, and Ki-67 expression in a human xenograft carcinoma model (29), but the relationship between tk-1 and Ki-67 expression is not evident in every carcinoma model, as Ki-67 represents a somewhat larger amount of the cell cycle than tk-1 (29). Brockenbrough et al recently suggested that the 18 F-FLT uptake may also be influenced by factors besides tk-1 activity, including competition with endogenous thymidine, transport via nucleoside transporters, the degradative metabolism of phosphorylated metabolites, and the rate of DNA repair (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ki-67 is an excellent immunohistochemical marker for proliferating cells and is exclusively present during all active phases of the cell cycle (G(1), S, G(2), and mitosis) but not in resting cells (G(0)) (36). Keen et al reported a strong correlation between 18 F-FLT uptake, tk-1 expression, and Ki-67 expression in a human xenograft carcinoma model (29), but the relationship between tk-1 and Ki-67 expression is not evident in every carcinoma model, as Ki-67 represents a somewhat larger amount of the cell cycle than tk-1 (29). Brockenbrough et al recently suggested that the 18 F-FLT uptake may also be influenced by factors besides tk-1 activity, including competition with endogenous thymidine, transport via nucleoside transporters, the degradative metabolism of phosphorylated metabolites, and the rate of DNA repair (37).…”
Section: Discussionmentioning
confidence: 99%
“…Because 18 F-FLT PET is frequently used in the pharmaceutical industry and by academic researchers to determine the response of anticancer drugs (29,(40)(41)(42), our imaging method may represent a useful tool for evaluating the impact of new therapeutics on cell proliferation both in experimental arthritis models and in humans. Additionally, PET/MR imaging and PET/CT are noninvasive techniques that enable longitudinal studies, allowing the investigation of a single subject at several time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDG PET/CT measures increased cellular glucose metabolism as expressed by the standardized uptake value (SUV). In oncologic imaging, increased SUV may be seen as a sign of increased cell proliferation [14] and may also correlate with the degree of tumour necrosis [5]. The principle of DW MRI as a functional biomarker is based on the assessment of random (Brownian) motion of extracellular water molecules, which is restricted in hypercellular tumour tissue, as expressed by the decreased apparent diffusion coefficient (ADC) value.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies also investigated the relationship between [ 18 F]FLT uptake and TK1, since [ 18 F]FLT uptake is considered to be a direct measure of TK1 activity as it peaks during the S-phase and found both strong [24,28] and weak correlations [27,29]. It is anticipated that therapeutic agents that, directly or indirectly, block the thymidine salvage pathway and thus TK1 activity decrease [ 18 F]FLT uptake.…”
Section: Discussionmentioning
confidence: 99%